Nonreceptor protein tyrosine phosphatases (NRPTPs) gene family associates with the risk of hepatocellular carcinoma in a Chinese hepatitis B virus‐related subjects - Shen, Na; Wang, Peng; Li, Ying; Zhu, Yaowu; Gong, Yajie; Zhong, Rong; Lu, Yanjun; Cheng, Liming (Molecular carcinogenesis, 2020)
Nonreceptor protein tyrosine phosphatases (NRPTPs) are reported to be associated with several human cancers, but their roles in hepatitis B virus (HBV)‐related hepatocellular carcinoma (HCC) remain unclear. Here, we integrated bioinformatics tools, population association analyses, and biological assays to systematically screen for potentially functional single nucleotide polymorphisms (SNPs) within the 17 NRPTPs genes and evaluate the effects of candidate SNPs on the risk of HCC or persistent HBV infection. A total of 790 HBV‐related HCC cases and 1454 cancer‐free controls were enrolled. Controls included 711 HBV persistent carriers and 743 spontaneously recovered subjects. Results demonstrated that PTPN4 rs9308777 (odds ratio [OR] = 1.25, 95% confidence interval [CI] = 1.06‐1.49, P = .009) and PTPN12 rs350050 (OR = 1.26, 95% CI = 1.10‐1.45, P = .001), were significantly associated with HCC risk, but not with persistent HBV infection risk. The cumulative risk effect of these two SNPs was more significantly increased the susceptibility to HCC (OR = 1.27, 95% CI = 1.14‐1.41, P = 2.40 × 10−5). Subsequent biological assays further revealed the potential pathogenesis that PTPN4 rs9308777 might decrease the gene expression, and PTPN12 rs3750050 might promote cell proliferation by attenuating PTPN12's inhibitory activity on EGFR/ERK pathway. In summary, our integrative study highlights that PTPN4 and PTPN12 are significantly associated with HBV‐related HCC risk, but do not influence persistent HBV infection. These findings shed light on the importance of the synergistic effects of regulatory and missense variants on the risk for HCC, and provide data to support personalized cancer medicine in the future.